Transport Processes in Porous Media - Coutelieris, Frank A.; Delgado, J.M.P.Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The subject of this book is to study the porous media and the transport processes occur there. As a first step, the authors discuss several techniques for artificial representation of porous. Afterwards, they describe the single and multi phase flows in simplistic and complex porous structures in terms of macroscopic and microscopic equations as well as of their analytical and numerical solutions. Furthermore, macroscopic quantities such as permeability are introduced and reviewed. The book also discusses with mass transport processes in the porous media which are further strengthen by experimental validation and specific technological applications. This book makes use of state-of-the-art techniques for the modeling of transport processes in porous structures, and considers of realistic sorption mechanisms. It the applies advanced mathematical techniques for upscaling of the major quantities, and presents the experimental investigation and application, namely, experimental methods for the measurement of relevant transport properties. The main benefit of the book is that it discusses all the topics related to transport in porous media (including state-of-the-art applications) and presents some of the most important theoretical, numerical and experimental developments in porous media domain, providing a self-contained major reference that is appealing to both the scientists and the engineers. At the same time, these topics encounter a variety of scientific and engineering disciplines, such as chemical, civil, agricultural, mechanical engineering. The book is divided in several chapters that intend to be a resume of the current state of knowledge for benefit of related professionals and scientists.
Fundamentals of Porous Structures -- Flow in Porous Media -- Transport Phenomena in Porous Structures -- Modeling of Transport Processes in Porous Materials -- Experimental Investigation of Transport in Porous Media -- Applications & Examples -- Conclusions & Recommendations.
Keywords: Engineering; Materials; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Engineering Thermodynamics, Heat and Mass Transfer; Soft and Granular Matter, Complex Fluids and Microfluidics; Continuum Mechanics and Mechanics of Materials